The application of young coconut waste processing technology to the women farmer group in Kertasari, Ciamis Regency, West Java - Riyadi, Slamet; Abidin, Zaenal; Setiawan, Tia; Adnan, Bahana Aditya (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2023)
Young coconut fruit is an agricultural commodity with high economic value. The utilization of young coconuts needs to be followed up with post-harvest handling, such as preservation, packaging, and storage because young coconuts are easily damaged. Currently, young coconut consumption is starting to increase because it is widely used as a toxin neutralizer or consumed to maintain body health and fitness. The problem that occurs among young coconut ice sellers is how to deal with young coconut shell waste. Therefore, there is a need for innovation that can help young coconut ice sellers to handle waste from young coconuts and turn the coconut waste into something useful. The solution for processing young coconut waste in this community service activity is carried out by processing young coconut waste into ready-to-use organic fertilizer and planting media. In addition to overcoming the problem of young coconut waste, this activity is aimed at enabling the Women Farmers Group to be able to utilize young coconut waste to be used as organic fertilizer and planting media by applying appropriate technology to reduce the impact of environmental pollution due to the abundance of this waste. As the results of these activities, the women farmer groups have been able to utilize young coconut waste to be used as material for making organic fertilizer and planting media which were initially not of economic value by using a chopping machine, so as to reduce the impact of environmental pollution caused by the abundance of this waste.